2018
DOI: 10.1590/1980-57642018dn12-030009
|View full text |Cite
|
Sign up to set email alerts
|

Formal language assessment in low-educated healthy subjects

Abstract: Although many studies have shown the influence of education on cognition, the impact of low education on the various cognitive functions appears to differ. The hypothesis of the present study is that, with regards to language, the use of parameters derived from populations with 5-8 years of education leads to false-positive results.Objective:to determine the influence of low education on the language tasks assessed by the MTL-Brazil BatteryMethods:30 healthy adults with 2-4 years of education were submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Because language and verbal fluency are cognitive skills directly dependent on attention and working memory, this study hypothesis was that there is a correlation between cognitive potential - P300 and language and verbal fluency. This hypothesis is supported by authors25 who believe that the production of language involves planning and monitoring. As such, language production is not a totally automatic task, because it requires cognitive processing.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Because language and verbal fluency are cognitive skills directly dependent on attention and working memory, this study hypothesis was that there is a correlation between cognitive potential - P300 and language and verbal fluency. This hypothesis is supported by authors25 who believe that the production of language involves planning and monitoring. As such, language production is not a totally automatic task, because it requires cognitive processing.…”
Section: Discussionmentioning
confidence: 74%
“…The limitations of this study involve the method used to collect data, which was via a cognitive screening instrument, as opposed to a specific battery for assessing language composed of multiple tasks providing greater precision in the assessment of each language skill 25. The screening instrument was used because the present study was part of a larger investigation conducted in the homes of elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These factors likely promoted the similar performance in carrying out the task (Medeiros & Ortiz, 2021). In addition, results of a previous study (Akashi & Ortiz, 2018) revealed the presence of a ceiling effect on this task among healthy individuals with low educational level. In turn, the absence of differences between groups in automatic speech and non-verbal praxis tasks were expected.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, greater demand is placed on working memory to process sentences with non-canonic structure, such as those with passive structures and center-embedded clauses, since the phrase must be first stored, then organized and syntactically decoded, for final comprehension of the information and selection of the correct drawing (Eom & Sung, 2016;Ortiz & Bertolucci, 2005). Previous studies have found differences in oral comprehension of sentences when groups with 1-4 years of formal education and 5-8 years of formal education were compared (Akashi & Ortiz, 2018) and even in comparison of 5-8 years of education to 8-12 years of education (Pagliarin et al, 2014) and, in this case, it can also be influenced by reading and writing habits (Pagliarin et al, 2015). Finally, the oral of text requires comprehension, retention and retrieval of the information presented in the text, recruiting working memory and components of executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tasks involving graphic stimuli (written comprehension, dictation, reading, written naming, number dictation, reading of numbers, written narrative, and written text comprehension) tend to be more sensitive to the influence of education (Ortiz, & Costa, 2011). The impact of schooling on written narratives could also be found even when comparing low educational level with a very low educational level (Akashi, & Ortiz, 2018).…”
Section: Discussionmentioning
confidence: 94%